2010
DOI: 10.5194/bg-7-513-2010
|View full text |Cite
|
Sign up to set email alerts
|

The African contribution to the global climate-carbon cycle feedback of the 21st century

Abstract: Abstract. Future climate change will have impact on global and regional terrestrial carbon balances. The fate of African tropical forests over the 21st century has been investigated through global coupled climate carbon cycle model simulations. Under the SRES-A2 socio-economic CO 2 emission scenario of the IPCC, and using the Institut Pierre Simon Laplace coupled ocean-terrestrial carbon cycle and climate model, IPSL-CM4-LOOP, we found that the warming over African ecosystems induces a reduction of net ecosyst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…As previously mentioned, the African vegetation contributes 38% of the global climate-carbon cycle feedback, mostly coming from its savanna comprised mainly of woodlands (Friedlingstein et al, 2010).…”
Section: Relationships Between Lsp and Rainfall Parametersmentioning
confidence: 94%
“…As previously mentioned, the African vegetation contributes 38% of the global climate-carbon cycle feedback, mostly coming from its savanna comprised mainly of woodlands (Friedlingstein et al, 2010).…”
Section: Relationships Between Lsp and Rainfall Parametersmentioning
confidence: 94%
“…We suggest that the observed decreasing trend in the contribution of R SOC to T SOC pool with increasing precipitation was mainly the result of more frequent fire events characteristic of savanna ecosystems. Global coupled climate carbon cycle model simulations predict net losses in SOC stocks in West Africa as a result of increased heterotrophic soil respiration and reduced precipitation (Friedlingstein et al, 2010). These models have identified that SOC losses will be more significant in humid coastal regions, while SOC pools will show lower susceptibility in more arid regions.…”
Section: Significance Of the Findings For Soil Carbon Studies In Tropmentioning
confidence: 99%
“…Modeling studies suggest large differences in different approaches used to obtain estimates of global GPP (Anav et al 2013), largely controlled by seasonal, decadal and longer time variability and change in different regions, globally (Ahlström et al 2015). Many studies have estimated GPP in key regions of the world: for example, Lee et al (2013) estimated GPP in Amazonia using Greenhouse gases Observing SATellite (GOSAT) measurements; Liu et al (2014) estimated GPP in China using five GPP models and Moderate Resolution Imaging Spectroradiometer (MODIS) observations; Jung et al (2008) estimated GPP in Europe (EU) using terrestrial ecosystem models; Nightingale et al (2008) and Chen et al (2011) estimated GPP in the USA using MODIS observations; and Friedlingstein et al (2010) estimated GPP in the Sahel region of Africa using ORCHIDEE model. In spite of this large body of research, there is limited information on the relative contributions of these regions to the seasonal, inter-annual and longer time variability of total global GPP.…”
Section: Introductionmentioning
confidence: 99%